ANALISIS PERUBAHAN PENGGUNAAN LAHAN DAN POLA PEMANFAATAN RUANG TERBUKA HIJAU PUBLIK DI KECAMATAN SUKOHARJO, KABUPATEN SUKOHARJO - Chatarina Muryani; Pipit Wijayanti; Niken Tri Nugraini (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
Development in an area results in a change in land use and a reduction in green open spaces, especially public green open spaces. The proportion of Public Green Open Space is 20% of the total area. Public Green Open Spaces are utilized by the general public with various activities. The area studied in this study is Sukoharjo District, with the research objectives (1) to determine changes in land use in 2005 and 2019, (2) to determine the availability and adequacy of Public Open Space in Sukoharjo District, (3) to determine patterns of utilization of Public Open Space in Sukoharjo District. The research uses descriptive qualitative analysis with observation and documentation methods with overlay data analysis techniques and Iconos image analysis. The population in this research is Public Green Open Space with purposive sampling technique. The results of the study show that there have been changes in land use in 2005 and 2019 for each land use, the availability and adequacy of public green open space in Sukoharjo District is only 1.1% of the total area, so it is still insufficient to meet the stated public green open space needs. Community activities in Public Green Open Space are very diverse, and these activities can be patterned according to the activities of utilizing Public Green Open Space in Sukoharjo District, including elongated, spreading, and grouped patterns.